The uses of the media in school physical education classes: Possibilities and difficulties - dos Diniz, Irlla Karla Santos [UNESP]; de Rodrigues, Heitor Andrade; Darido, Suraya Cristina [UNESP] (Universidade Federal do Rio Grande do Sul, 2012)
The media through images, sounds and information influences the way students interpret reality. This way, there is the need for the school to reflect on these issues and create teaching strategies to take advantage of this apparatus. The objective of this research was to analyze some possibilities of a proposal that addressed the content body culture through reports published by the newspaper Folha de São Paulo in Physical Education classes. The data indicated the media as a good teaching resource for classes of this course, since the students considered enriching classes for learning.
Os usos da mídia em aulas de educação física escolar: Possibilidades e dificuldades
Keywords: School physical education; Social media; Teaching materials